The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1089/dia.2008.0034
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Evaluation of Nine Instruments for Self-Monitoring of Blood Glucose

Abstract: The quality of instruments for SMBG seems to have improved during recent years, although there are still analytical problems. A standardized evaluation protocol is necessary and should be regularly revised taking into account the development of new technology and the needs of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 26 publications
3
49
1
3
Order By: Relevance
“…System accuracy and other performance data of the systems investigated have also been reported in other studies. [9][10][11][12][13][14][15][16][17][18][19] However, in our study, each system was evaluated by using 2 established comparison methods/systems, a GOD-based method/YSI 2300 STAT Plus glucose analyzer and a HK-based method/cobas c111 analyzer; the use of 2 methods allows for an investigation of possible impacts of the used comparison method/system on system accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…System accuracy and other performance data of the systems investigated have also been reported in other studies. [9][10][11][12][13][14][15][16][17][18][19] However, in our study, each system was evaluated by using 2 established comparison methods/systems, a GOD-based method/YSI 2300 STAT Plus glucose analyzer and a HK-based method/cobas c111 analyzer; the use of 2 methods allows for an investigation of possible impacts of the used comparison method/system on system accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…7 Another study found that 3 of 9 meters failed the ISO standard when testing was performed by patients, 12 while another study revealed that, during patient use of 21 GMs, 16% of BG measurements were more than 20% above or below the reference value. 13 The total error found in this GM testing is far greater than the current ISO standard of 5% or less. The authors suggested that, since "inaccurate BG monitoring systems bear the risk of false treatment decisions by the diabetes patient and subsequent possible severe health injury, manufacturers should regularly and effectively check the quality of BG meters and BG test strips."…”
Section: Re-certification For Determination Of Accuracy Post-food Andmentioning
confidence: 64%
“…Insiders know how important it is to choose a "good" batch of test strips so that a BG test system can pass a test (e.g., for approval) and that there are considerable batch-to-batch differences in measurement quality. 5 This variability between batches of test strips can even exceed the acceptance limits of the present ISO norm. 6,7 We believe that it is mandatory that an independent professional institution sytematically evaluate the measurement quality of BG test systems under daily life conditions with random samples, even years after approval, because this task cannot be delegated to the people with diabetes.…”
Section: Evaluation Of the Performance Quality Of Blood Glucose Test mentioning
confidence: 97%